2012
DOI: 10.1111/j.1475-1313.2012.00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Vision and cricket

Abstract: This review discusses the hypothesis that hitting a cricket ball depends on predicting the instant that the ball will be located in the volume of space within which it can be successfully hit, and that this prediction is based on retinal image correlates of the direction of motion in depth and the time to collision (or time to passage). The performance of top cricket players allows an estimation of their accuracy in this spatio-temporal prediction. The bowler challenges the batsman's skill by (1) causing the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…As perceptual and motor learning use similar cortical pathways,16 VPL might have an impact on all types of sports that require excellent vision. Visual training is already part of the training schedule of professional baseball and cricket players 17 18. In conclusion, we found that repetitive tests of VA improved vision in young athletes.…”
Section: Discussionsupporting
confidence: 55%
“…As perceptual and motor learning use similar cortical pathways,16 VPL might have an impact on all types of sports that require excellent vision. Visual training is already part of the training schedule of professional baseball and cricket players 17 18. In conclusion, we found that repetitive tests of VA improved vision in young athletes.…”
Section: Discussionsupporting
confidence: 55%
“…Our best subjects (S 6 , S 7 , S 8 , and S 9 ) showed tracking gain values within a wide range [0.65–0.98] (maximum and minimum average values within each caught trial observed throughout the experimental session), and time lags within a similarly wide range [1.6–98 ms] during pursuit in the case of caught trials. Thus, the analysis of the gaze tracking accuracy might not be informative of the visual signal processing which subserves motor control execution in our task, as argued by other studies [ 1 , 3 , 31 , 41 ]. For instance, information on target motion may be gathered peripherally as suggested in [ 2 , 17 ].…”
Section: Discussionmentioning
confidence: 83%
“…In cricket, a sport similar to baseball, Elmurr described 7 the distinction between “hardware”, the actual visual system; vs. “software”, the processing of visual information. Regan proposed 8 that cricket batters must predict precisely when and where a pitched ball will be located in order for batting success, while Brenton et al . described 9 the use of electronic glasses to occlude vision soon after the pitcher released the ball, forcing the batter to rely on the prediction of ball movement for batting success.…”
Section: Introductionmentioning
confidence: 99%